Alkali-activated solid waste-based cementing material as well as preparation method and application thereof

By using alkaline stimulation of solid waste gel materials, the problem of resource consumption and environmental pollution during production and use of cement stable gravel semi -rigidity in production and use has been solved. 性能和早期微膨胀效果。

CN119371124APending Publication Date: 2025-01-28GANSU PROVINCE TRANSPORTATION PLANNING SURVEY & DESIGN INST
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202410719189.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing cement-stabilized gravel semi-rigid base layer consumes a large amount of non-renewable resources during production and use, and emits a large amount of carbon dioxide, resulting in poor environmental and economic benefits.

Method used

The use of alkali -stimmed solid waste -based gel materials, which uses industrial solid waste as the substrate, including flour ash, mine powder, cement, phosphide, composite excitation agent, and enhanced outer agent. Hydrating activity has formed a gel material with high -powered performance and early micro -expansion effects.

Benefits of technology

Realized low -cost and environmentally friendly road engineering semi -rigid grass -roots materials, with excellent mechanical properties and early micro -expansion effects, suitable for different types of semi -rigid grass -roots aggregate, reduce dependence on non -renewable resources and reduce carbon dioxide emissions with carbon dioxide emissions Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371124A_ABST
    Figure CN119371124A_ABST
Patent Text Reader

Abstract

The invention provides an alkali-activated solid waste-based cementing material as well as a preparation method and application thereof, and relates to the technical field of building materials. The alkali-activated solid waste-based cementing material provided by the invention is prepared from the following components in percentage by mass: 50 to 75 percent of fly ash, 15 to 30 percent of mineral powder, 5 to 10 percent of cement, 2 to 8 percent of phosphogypsum, 0.5 to 3.5 percent of composite exciting agent and 0.01 to 0.07 percent of reinforcing additive. The cement, the industrial solid waste fly ash, the mineral powder and the ardealite are taken as main raw materials, so that the low-cost and environment-friendly effects are achieved, and meanwhile, the resource utilization rate of the industrial solid waste is increased. The fly ash and the mineral powder have potential hydration activity and have gelling property and curing property; the ardealite has the effects of adjusting the setting time and the early expansion rate, and the reinforcing admixture has the effects of retaining water, reducing water and reducing pores, so that the early shrinkage and strength of the alkali-activated solid waste-based cementing material can be effectively controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to an alkali-activated solid waste-based gelling material and a preparation method and application thereof. Background Art

[0002] Semi-rigid base is the main structural form of road base. In the existing technology, cement-stabilized gravel semi-rigid base is the most widely used semi-rigid base. Cement, as an inorganic binder for stabilizing gravel, is used in large quantities in semi-rigid base. However, the "two grinding and one burning" process in cement production consumes a large amount of non-renewable resources such as lime and coal, and cement production and use emit a large amount of carbon dioxide. From the perspective of environmental and economic benefits, the use of cement-stabilized gravel semi-rigid base is not the best choice. Summary of the invention

[0003] The purpose of the present invention is to provide an alkali-activated solid waste-based cementitious material and a preparation method and application thereof. The present invention uses industrial solid waste as a substrate, has low material cost and is environmentally friendly; and the alkali-activated solid waste-based cementitious material of the present invention is used for stabilizing semi-rigid base gravel in road engineering, and has excellent mechanical properties and early micro-expansion effects.

[0004] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:

[0005] An alkali-activated solid waste-based cementitious material, comprising the following components by mass fraction:

[0006]

[0007] The composite activator includes a solid waste-based activator and a chemical activator; the solid waste-based activator is carbide slag; the chemical activator includes one or more of sodium hydroxide, sodium carbonate, sodium metasilicate pentahydrate, sodium metasilicate nonahydrate and potassium hydroxide.

[0008] Preferably, the reinforcing admixture is one or more of a water retaining agent, a water reducing agent and a defoaming agent.

[0009] Preferably, the fineness of the fly ash is such that the residue passing through a 325-mesh square-hole sieve is ≤30wt.%; and the standard consistency water-cement ratio of the fly ash is 0.24-0.30.

[0010] Preferably, the fineness of the mineral powder is such that the residue passing through a 175-mesh square-hole sieve is ≤10wt.%; and the standard consistency water-cement ratio of the mineral powder is 0.3-0.35.

[0011] Preferably, the mineral powder is granulated blast furnace slag powder; the specific surface area of ​​the mineral powder is ≥400m 2 / kg.

[0012] Preferably, the moisture content of the phosphogypsum is less than 1wt.%, and the crystal water content is 11-16wt.%; the fineness of the phosphogypsum is such that the residue on the sieve of a 175-mesh square hole sieve is less than 10wt.%.

[0013] Preferably, the fineness of the solid waste-based activator is such that the residue passing through a 175-mesh square hole sieve is ≤10wt.%.

[0014] The present invention also provides a method for preparing the alkali-activated solid waste-based gelling material according to the above technical solution, comprising the following steps:

[0015] The alkali-activated solid waste-based cementitious material is obtained by mixing fly ash, mineral powder, cement, phosphogypsum, a composite activator and a reinforcing admixture.

[0016] The present invention also provides the use of the alkali-activated solid waste-based cementitious material described in the above technical solution or the alkali-activated solid waste-based cementitious material prepared by the preparation method described in the above technical solution in the stabilization of semi-rigid base gravel in road engineering.

[0017] The present invention provides an alkali-activated solid waste-based cementitious material, which comprises the following components by mass fraction: 50-75% fly ash, 15-30% mineral powder, 5-10% cement, 2-8% phosphogypsum, 0.5-3.5% composite activator and 0.01-0.07% reinforcing admixture; the composite activator comprises a solid waste-based activator and a chemical activator; the solid waste-based activator is carbide slag; the chemical activator comprises one or more of sodium hydroxide, sodium carbonate, sodium metasilicate pentahydrate, sodium metasilicate nonahydrate and potassium hydroxide. The present invention uses cement and industrial solid waste fly ash, mineral powder and phosphogypsum as main raw materials, has low cost and environmentally friendly effects, and at the same time improves the resource utilization rate of industrial solid waste. In the present invention, fly ash and mineral powder, which are bulk industrial solid wastes, have potential hydration activity, and their hydration activity is stimulated by a composite activator (the main components of fly ash and mineral powder are aluminosilicates mainly composed of SiO2 and Al2O3, and the covalent bonds of Si-O-Si, Si-O-Al, Al-O-Al, etc. in the aluminosilicate raw materials are broken by the action of OH- to generate single ion groups or ion groups with a lower degree of polymerization. Under the condition of pH ≥ 9, they are polymerized into an aluminosilicate structure different from the raw materials, and have gelling and curing properties. The main chain of this structure is composed of -Si-O-Al-O-Si-O-); phosphogypsum has the function of regulating the setting time and regulating the early expansion rate, and the reinforcing admixture has the functions of retaining water, reducing water and reducing porosity, which can effectively control the early shrinkage and strength of alkali-activated solid waste-based cementitious materials.

[0018] The alkali-activated solid waste-based cementitious material provided by the present invention is used for stabilizing semi-rigid base gravel in road engineering and has the advantages of low cost, environmental friendliness, early micro-expansion, convenient engineering application, high compressive strength, and good adaptability to different types of semi-rigid base aggregates. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0020] Figure 1 and Figure 2 This is a comparison chart of cracks in the stabilized base layer of the alkali-activated solid waste-based cementitious material described in Example 1 and the cement stabilized base layer. DETAILED DESCRIPTION

[0021] The present invention provides an alkali-activated solid waste-based gelling material, which comprises the following components by mass fraction:

[0022]

[0023] The composite activator includes a solid waste-based activator and a chemical activator; the solid waste-based activator is carbide slag; the chemical activator includes one or more of sodium hydroxide, sodium carbonate, sodium metasilicate pentahydrate, sodium metasilicate nonahydrate and potassium hydroxide.

[0024] In the present invention, unless otherwise specified, all components are commercially available products well known to those skilled in the art.

[0025] In the present invention, the alkali-activated solid waste-based cementitious material includes 50-75% fly ash, preferably 52-62%, and more preferably 55%, by mass fraction. In the present invention, the type of fly ash is preferably primary fly ash or secondary fly ash. In the present invention, the fineness of the fly ash is preferably ≤30wt.% of the sieve residue passing through a 325-mesh square hole sieve, and more preferably 15-20wt.%; the standard consistency water-cement ratio of the fly ash is preferably 0.24-0.30, and more preferably 0.26-0.28. In the present invention, fly ash is the main matrix material of the alkali-activated solid waste-based cementitious material, and fly ash is usually fine particles precipitated in the ash after solid fuel is burned in an industrial furnace; its main chemical components are SiO2 and Al2O3, in which the Si-O bonds and Al-O bonds will break under certain alkaline conditions and form SiO4 - and AlO4 - Monomer, along with SiO4 - and AlO4- As the monomer concentration increases, dimers, trimers and other oligomers begin to form. As the condensation reaction proceeds, the monomers and oligomers interact and link to form a polymer with a three-dimensional network structure and interconnectedness, which then solidifies into a geopolymer gel through dehydration condensation.

[0026] In the present invention, the alkali-activated solid waste-based cementitious material includes 15-30% of mineral powder, preferably 21-39.5%, and more preferably 30% by mass fraction. In the present invention, the mineral powder is preferably granulated blast furnace slag powder; the main components of the mineral powder are preferably SiO2 37.08wt.%, CaO 32.06wt.%, Al2O3 10.71wt.%, MgO 8.37wt.%, MnO2.44wt.%, SO3 1.93wt.% and TiO2 0.98wt.%. In the present invention, the fineness of the mineral powder is preferably ≤10wt.% of the sieve residue passing through a 175-mesh square hole sieve, and is more preferably 5-8wt.%; the standard consistency water-cement ratio of the mineral powder is preferably 0.3-0.35, and more preferably 0.32-0.33; the specific surface area of ​​the mineral powder is preferably ≥400m 2 / kg, more preferably 450 to 500 m 2 In the present invention, the mass coefficient of the mineral powder is preferably greater than 1.2, and more preferably 1.6 to 1.8.

[0027] In the present invention, the alkali-activated solid waste-based cementitious material includes 5-10% cement, preferably 6-8% by mass fraction. In the present invention, the cement is preferably labeled 42.5. In the present invention, the tricalcium aluminate mineral in the cement has a fast hydration rate, and the hydration product of the tricalcium aluminate can react with phosphogypsum to form calcium vanadium, which has micro-expansion and can well ensure the early expansion of the alkali-activated solid waste-based cementitious material.

[0028] In the present invention, the alkali-activated solid waste-based cementitious material includes 2-8% phosphogypsum, preferably 4-5% by mass fraction. In the present invention, the crystal water content of the phosphogypsum is preferably 11-16wt.%, more preferably 14wt.%. In the present invention, the fineness of the phosphogypsum is preferably ≤10wt.% through a 175-mesh square hole sieve, more preferably 6-8wt.%. In the present invention, the water content of the phosphogypsum is preferably <1wt.%, more preferably 0.6-0.8wt.%. In the present invention, if the water content of the phosphogypsum raw material is higher than 1wt.%, the present invention preferably dries the phosphogypsum to a water content lower than 1wt.%; the drying temperature is preferably 105±2°C. In the present invention, the phosphogypsum mainly acts as a reactant for retarding setting and generating calcium vanadium. The phosphogypsum reacts with tricalcium aluminate to generate calcium vanadium, and the calcium vanadium is wrapped on the surface of the unreacted material particles to delay the hydration process and achieve the purpose of retarding setting.

[0029] In the present invention, the alkali-activated solid waste-based cementitious material includes 0.5-3.5% of the composite activator, preferably 2.5-3%, by mass fraction. In the present invention, the composite activator includes a solid waste-based activator and a chemical activator; the solid waste-based activator is carbide slag. In the present invention, the fineness of the solid waste-based activator is preferably ≤10wt.% of the sieve residue passing through a 175-mesh square hole sieve, and more preferably ≤6wt.%. In the present invention, the carbide slag is the waste residue with calcium hydroxide as the main component after acetylene gas is obtained by hydrolyzing calcium carbide. The carbide slag has a high alkalinity and can be used as an alkali activator.

[0030] In the present invention, the chemical stimulant includes one or more of sodium hydroxide, sodium carbonate, sodium metasilicate pentahydrate, sodium metasilicate nonahydrate and potassium hydroxide, preferably sodium metasilicate pentahydrate. In the present invention, the mass ratio of the solid waste-based stimulant to the chemical stimulant is preferably 2-8:1-7, more preferably 3-7:1-5.

[0031] In the present invention, the alkali-activated solid waste-based cementitious material includes 0.01-0.07% reinforcing admixture, preferably 0.02-0.04%, and more preferably 0.03% by mass fraction. In the present invention, the reinforcing admixture is preferably one or more of a water retaining agent, a water reducing agent, and a defoaming agent. In the present invention, the water retaining agent is preferably a water-absorbing resin; the water reducing agent is preferably a polycarboxylic acid water reducing agent; the defoaming agent is preferably a fatty alcohol ether or fatty alcohol ester defoaming agent. In the present invention, when the reinforcing admixture is preferably a water reducing agent and a water retaining agent, the mass ratio of the water reducing agent and the water retaining agent is preferably 2-8:2-5, and more preferably 5-6:4-5. In the present invention, when the reinforcing admixture is preferably a water reducing agent, a water retaining agent, and a defoaming agent, the mass ratio of the water reducing agent, the water retaining agent, and the defoaming agent is preferably 4-9:1-5:1-5, and more preferably 4:3:3. In the present invention, the water reducing agent in the reinforcing admixture plays a role in reducing water and activating the surface, and the water retaining agent plays a role in alleviating the water loss of the base layer, which can effectively alleviate the cracking of the base layer.

[0032] The present invention also provides a method for preparing the alkali-activated solid waste-based gelling material according to the above technical solution, comprising the following steps:

[0033] The alkali-activated solid waste-based cementitious material is obtained by mixing fly ash, mineral powder, cement, phosphogypsum, a composite activator and a reinforcing admixture.

[0034] The present invention mixes fly ash, mineral powder, cement, phosphogypsum, a composite activator and a reinforcing admixture to obtain the alkali-activated solid waste-based cementitious material. In the present invention, the mixing is preferably ball milling mixing. The present invention does not impose any special restrictions on the equipment and technical solutions for the ball milling mixing, and the ball milling equipment and ball milling technical solutions familiar to those skilled in the art can be used. In the present invention, after the mixing, it is also preferred to pass through a 175-mesh square hole sieve; the sieve residue after passing through the 175-mesh square hole sieve is preferably ≤10wt.%, more preferably 2-8wt.%, and further preferably 4-6wt.%.

[0035] In the present invention, the method for preparing the alkali-activated solid waste-based gelling material preferably further comprises the following steps:

[0036] The fly ash, mineral powder, phosphogypsum and cement are first mixed to obtain a solid waste-based mixture; the solid waste-based mixture, a composite activator and a reinforcing admixture are second mixed to obtain the alkali-activated solid waste-based cementitious material.

[0037] In the present invention, the first mixing and the second mixing are preferably stirred mixing; the time of the first mixing and the second mixing is independently preferably 8 to 10 minutes; the rotation speed is independently preferably 85 to 95 r / min, more preferably 86 to 90 r / min.

[0038] The present invention also provides the use of the alkali-activated solid waste-based cementitious material described in the above technical solution or the alkali-activated solid waste-based cementitious material prepared by the preparation method described in the above technical solution in the stabilization of semi-rigid base gravel in road engineering.

[0039] In order to further illustrate the present invention, the alkali-activated solid waste-based gelling material provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0040] Example 1

[0041] The sources and proportions of the raw materials used in Example 1 are shown in Table 1:

[0042] Table 1 Sources and proportions of raw materials for alkali-activated solid waste-based cementitious materials in Example 1

[0043]

[0044] Note: The content of reinforcing admixture is the proportion of the total mass of fly ash, mineral powder, cement, phosphogypsum and composite activator.

[0045] The raw materials are weighed and set aside according to the proportions described in Table 1. The composite activator in Table 1 is sodium metasilicate pentahydrate and carbide slag in a mass ratio of 1:2; the reinforcing admixture is a polycarboxylic acid high-efficiency water-reducing agent and a water-absorbing resin in a mass ratio of 5:5.

[0046] The fly ash, mineral powder, cement and phosphogypsum weighed for use are added into a mixing tank for stirring at a speed of 86 r / min for 8 to 10 min to obtain a solid waste-based mixed material;

[0047] The reserved composite activator, reinforcing admixture and the above-mentioned solid waste-based mixed material are weighed and added into a stirring tank for stirring at a speed of 86 r / min and a stirring time of 8 to 10 minutes to obtain an alkali-activated solid waste-based cementitious material.

[0048] The mortar index of alkali-activated solid waste-based cementitious materials was tested according to the provisions of GB / T 35162-2017 "Slow-setting Portland Cement for Road Base", and the test results are shown in Table 2:

[0049] Table 2 Test results of technical indicators of alkali-activated solid waste-based cementitious materials described in Example 1

[0050]

[0051]

[0052] The alkali-activated solid waste-based cementitious material described in Example 1 was used as an inorganic stabilizing material, and a 100km semi-rigid base layer of alkali-activated solid waste-based cementitious material stabilized gravel mixture was applied in the G331 Dahuo project. Complete core samples were drilled 14 days after the paving of the alkali-activated solid waste-based cementitious material base layer, and the core sample strength was greater than 14MPa, meeting the design requirements.

[0053] Table 3 Crack test data of stabilized base of alkali-activated solid waste-based cementitious materials and cement stabilized base in Example 1

[0054]

[0055] Figure 1 and Figure 2 This is a comparison of cracks in the stabilized base of the alkali-activated solid waste-based cementitious material and the cement stabilized base described in Example 1. Figure 1 As shown in Table 3, the overall cracks in the G331 Dahuo project using alkali-activated solid waste-based cementitious material base were reduced by more than 60% in the DHSG1 and DHSG1 standards compared with the cement-stabilized base.

[0056] Example 2

[0057] The sources and proportions of the raw materials used in Example 2 are shown in Table 4:

[0058] Table 4 Sources and proportions of raw materials for alkali-activated solid waste-based cementitious materials in Example 2

[0059]

[0060]

[0061] Note: The content of reinforcing admixture is the proportion of the total mass of fly ash, mineral powder, cement, phosphogypsum and composite activator.

[0062] The raw materials are weighed and set aside according to the proportions described in Table 4. The composite activator in Table 4 is sodium metasilicate pentahydrate and carbide slag in a mass ratio of 1:8; the reinforcing admixture is a polycarboxylic acid high-efficiency water-reducing agent and a water-absorbing resin in a mass ratio of 6:4.

[0063] The fly ash, mineral powder, cement and phosphogypsum weighed for use are added into a mixing tank for stirring at a speed of 86 r / min for 8 to 10 min to obtain a solid waste-based mixed material;

[0064] The reserved composite activator, reinforcing admixture and the above-mentioned solid waste-based mixed material are weighed and added into a stirring tank for stirring at a speed of 86 r / min and a stirring time of 8 to 10 minutes to obtain an alkali-activated solid waste-based cementitious material.

[0065] The mortar index was tested according to GB / T 35162-2017 "Slow-setting Portland Cement for Road Base", and the test results are shown in Table 5:

[0066] Table 5 Test results of technical indicators of alkali-activated solid waste-based cementitious materials in Example 2

[0067]

[0068] Example 3

[0069] The sources and proportions of the raw materials used in Example 3 are shown in Table 6:

[0070] Table 6 Sources and proportions of raw materials for alkali-activated solid waste-based cementitious materials in Example 3

[0071]

[0072]

[0073] Note: The content of reinforcing admixture is the proportion of the total mass of fly ash, mineral powder, cement, phosphogypsum and composite activator.

[0074] The raw materials are weighed and set aside according to the proportions described in Table 6. The composite activator in Table 6 is sodium metasilicate pentahydrate and carbide slag in a mass ratio of 1:2; the reinforcing admixture is a polycarboxylic acid high-efficiency water reducing agent, a water-absorbing resin and a fatty alcohol ether defoaming agent in a mass ratio of 4:3:3.

[0075] The fly ash, mineral powder, cement and phosphogypsum weighed for use are added into a mixing tank for stirring at a speed of 86 r / min for 8 to 10 min to obtain a solid waste-based mixed material;

[0076] The reserved composite activator, reinforcing admixture and the above-mentioned solid waste-based mixed material are weighed and added into a stirring tank for stirring at a speed of 86 r / min and a stirring time of 8 to 10 minutes to obtain an alkali-activated solid waste-based cementitious material.

[0077] The mortar index was tested according to GB / T 35162-2017 "Slow-setting Portland Cement for Road Base", and the test results are shown in Table 7:

[0078] Table 7 Test results of technical indicators of alkali-activated solid waste-based cementitious materials in Example 3

[0079]

[0080] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An alkali-activated solid waste-based gelling material, characterized in that: By mass fraction, it includes the following components: The composite activator includes a solid waste-based activator and a chemical activator; the solid waste-based activator is carbide slag; the chemical activator includes one or more of sodium hydroxide, sodium carbonate, sodium metasilicate pentahydrate, sodium metasilicate nonahydrate and potassium hydroxide.

2. The alkali-activated solid waste-based gelling material according to claim 1, characterized in that: The reinforcing admixture includes one or more of a water retaining agent, a water reducing agent and a defoaming agent.

3. The alkali-activated solid waste-based gelling material according to claim 1, characterized in that: The fineness of the fly ash is that the residue passing through a 325-mesh square-hole sieve is ≤30wt.%; the standard consistency water-cement ratio of the fly ash is 0.24-0.

30.

4. The alkali-activated solid waste-based gelling material according to claim 1, characterized in that: The fineness of the mineral powder is that the residue passing through a 175-mesh square-hole sieve is ≤10wt.%; the standard consistency water-cement ratio of the mineral powder is 0.3-0.

35.

5. The alkali-activated solid waste-based gelling material according to claim 1 or 4, characterized in that: The mineral powder is granulated blast furnace slag powder; the specific surface area of ​​the mineral powder is ≥400m 2 / kg.

6. The alkali-activated solid waste-based gelling material according to claim 1, characterized in that: The moisture content of the phosphogypsum is less than 1wt.%, and the crystal water content is 11-16wt.%. The fineness of the phosphogypsum is such that the residue after passing through a 175-mesh square hole sieve is less than 10wt.%.

7. The alkali-activated solid waste-based gelling material according to claim 1, characterized in that: The solid waste-based activator has a fineness of 10 wt.% or less when the residue passes through a 175-mesh square-hole sieve.

8. The method for preparing the alkali-activated solid waste-based gelling material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The alkali-activated solid waste-based cementitious material is obtained by mixing fly ash, mineral powder, cement, phosphogypsum, a composite activator and a reinforcing admixture.

9. Use of the alkali-activated solid waste-based cementitious material according to any one of claims 1 to 7 or the alkali-activated solid waste-based cementitious material prepared by the preparation method according to claim 8 in the stabilization of semi-rigid base gravel in road engineering.

Citation Information

Cited By

  • Low-carbon composite cementing material for deep foundation pit engineering and preparation method of low-carbon composite cementing material

    CN119954478A

  • Alkali-activated solid waste-based supercapacitor and preparation method thereof

    CN120727483A